Exploring microplastic ingestion by three deep-water elasmobranch species: A case study from the Tyrrhenian Sea. (October 2019) - Valente, Tommaso; Sbrana, Alice; Scacco, Umberto; Jacomini, Carlo; Bianchi, Jessica; Palazzo, Luca; de Lucia, Giuseppe Andrea; Silvestri, Cecilia; Matiddi, Marco
Abstract: This study analyzes microplastic ingestion by three deep-water elasmobranch species ( Galeus melastomus, Scyliorhinus canicula and Etmopterus spinax ) from the Tyrrhenian Sea, discriminating between stomach and intestine contents. The absence of significant differences in frequency and abundance of plastic items into stomachs seems to suggest that ecological diversity among the three sharks does not strongly influence the probability of plastic ingestion in the study area. On the other hand, the detected differences in the microplastic content into the intestine might be due to a different retention time of microplastics, suggesting how feeding habits could influence metabolic features, and therefore affect the recovery of ingested plastic items. This information would improve the future development of marine micro-litter monitoring systems, following the MSFD requirements. Moreover, this study shows that all the three examined elasmobranch species can give important information even with relatively small sample sizes (N ≈ 30), and they could be used as target species for monitoring micro-litter ingestion in deep-water habitats. Graphical abstract: Image 1 Highlights: New proposal for study microplastic presence into stomach and intestine separately. Deep-water sharks are exposed to microplastic ingestion. First evidence of plastic ingestion by S. canicula in the Mediterranean Sea. Retention time affect the recovery of ingested microplastics. Elasmobranchs could be used for monitoring micro-litter ingestion. Abstract : Feeding habits could influence the retention time of ingested microplastics, and therefore affect their recovery.